Inhibition of focal adhesion kinase 2 results in a macrophage polarization shift to M2 which attenuates local and systemic inflammation and reduces heterotopic ossification after polysystem extremity trauma - Rowe, Cassie J.; Nwaolu, Uloma; Salinas, Daniela; Hong, Jonathan; Nunez, Johanna; Lansford, Jefferson L.; McCarthy, Conor F.; Potter, Benjamin K.; Levi, Benjamin H.; Davis, Thomas A. (Frontiers in Immunology, 2023)
Heterotopic ossification (HO) is a complex pathology often observed in combat injured casualties who have sustained severe, high energy polytraumatic extremity injuries. Once HO has developed, prophylactic therapies are limited outside of surgical excision. Tourniquetinduced ischemia injury (IR) exacerbates trauma-mediated musculoskeletal tissue injury, inflammation, osteogenic progenitor cell development and HO formation. Others have shown that focal adhesion kinase-2 (FAK2) plays a key role in regulating early inflammatory signaling events. Therefore, we hypothesized that targeting FAK2 prophylactically would mitigate extremity trauma induced IR inflammation and HO formation. We tested whether the continuous infusion of a FAK2 inhibitor (Defactinib, PF-573228; 6.94 µg/kg/min for 14 days) can mitigate ectopic bone formation (HO) using an established blast-related extremity injury model involving femoral fracture, quadriceps crush injury, three hours of tourniquet-induced limb ischemia, and hind limb amputation through the fracture site. Tissue inflammation, infiltrating cells, osteogenic progenitor cell content were assessed at POD-7. Micro-computed tomography imaging was used to quantify mature HO at POD-56. In comparison to vehicle control-treated rats, FAK2 administration resulted in no marked wound healing complications or weight loss. FAK2 treatment decreased HO by 43%. At POD-7, marked reductions in tissue proinflammatory gene expression and assayable osteogenic progenitor cells were measured, albeit no significant changes in expression patterns of angiogenic, chondrogenic and osteogenic genes. At the same timepoint, injured tissue from FAK-treated rats had fewer infiltrating cells. Additionally, gene expression analyses of tissue infiltrating cells resulted in a more measurable shift from an M1 inflammatory to an M2 anti-inflammatory macrophage phenotype in the FAK2 inhibitortreated group. Our findings suggest that FAK2 inhibition may be a novel strategy to dampen trauma-induced inflammation and attenuate HO in patients at high risk as a consequence of severe musculoskeletal polytrauma.